Pengaruh Layout, Kelengkapan Produk, Dan Persepsi Harga Terhadap Keputusan Pembelian: (Survei Pada Konsumen Toko Sembako Dua Putri Kab. Tasikmalaya) - Aulia Nur Fitriani (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
: This study aims to determine and analyze the effect of Layout, Product Completeness, and Price Perception on Purchase Decisions at the Dua Putri Sembako Store, Kab. Tasikmalaya. The method used in this research is a quantitative approach with a survey method. The population in this study amounted to 100 respondents. The type of data used in this study is primary data obtained from questionnaires. The data analysis used is the classical assumption test and multiple regression analysis using SPSS version 25. The results of this study indicate that the layout, product completeness, and price perception simultaneously have a significant effect on purchasing decisions at the Dua Putri Sub-District Store. Tasikmalaya. The layout partially has a significant effect on the Purchase Decision of the Dua Putri Sembako Store, Kab. Tasikmalaya. The completeness of the product partially has a significant effect on the Purchase Decision of the Dua Putri Sembako Store, Kab. Tasikmalaya. Price perception partially has a significant effect on the Purchase Decision of the Dua Putri Sembako Store, Kab. Tasikmalaya.